Milk composition of Holstein cows: a retrospective study - Bondan,Carlos (2018)
ABSTRACT: Worldwide, milk analysis is an satisfactory measurement of milk quality on dairy farms. Milk composition is the base for payment systems, so knowledge of its characteristics at different periods is essential for modern dairy producer. The aim of the study was to evaluate the effects of year, season, stage of lactation, and lactation number on variations in milk yield and composition of Holstein cows (n=148,604). Milk yield estimated by multiple regression was 25,50L/cow/day. Winter was the season with the highest milk yield and the highest protein and lactose content. Milk fat was highest in the fall, in cows in late lactation and also in primiparous cows. Lactating cows from 6 to 60 days in lactation and those in 2nd or 3rd lactation showed the highest milk yield. Lactose concentration was positively correlated with milk yield. Somatic cell score was negatively correlated with milk yield and with lactose concentration. Most important variations in milk characteristics occur among seasons, lactation stages and parities. Mammary gland health is yet the greatest challenge to be overcome.